Management of Education-Based Community Empowerment Programs to Increase Students Literacy Interest in the Pagergageung District Area, Tasikmalaya Regency - cipta, samudra eka; Sapitri, Riris; Kurniawan, Pendi (Jurnal Ilmiah Mandala Education (JIME), 2025)
This article examines the community empowerment program carried out by KKN students at the Indonesian Education University Bandung (UPI) as a strategy to improve students' literacy skills in the Pageragueng District, Tasikmalaya Regency. The article also discusses several programs including: literacy houses, literacy camps, teaching at the elementary level (diniyah), and learning assistance for students with special needs in the Pagerageung Tasikmalaya District area. This series of activities was carried out offline involving several stakeholders such as the Bina Warga Hasani Foundation and the Suryalaya Tasikmalaya Islamic Boarding School Education Foundation which is considered to have made the empowerment program activities a success. The results obtained were that the people in the Pagergagueng Tasikmalaya area were very enthusiastic, especially students who were greatly helped by the empowerment program in the area. The approach used in this article is to use a field observation and qualitative approach to discuss it in detail in this article.